Inverted Pedagogy In Higher Education: Rethinking University Teaching In Algeria And Engaging Students In Their Education - Asma Beyat , Fatiha Zenagui , Abderrahmane Hachi (Migration Letters, 2024)
The focus of this article is on the implementation of flipped classrooms in higher education in Algeria, specifically how it affects student engagement and personalized learning for third-year French language and literature undergraduates at the University of El-Oued. Using an experimental approach, we compare results before and after the introduction of flipped pedagogy, assessing the development of student’s autonomy and interaction. This research provises insights into the effectiveness of flipped pedagogy in this setting, suggesting avenues for reimagining university teaching in Algeria and more engaging students in their education.